Government Finance Statistics in the Countries of the Former Soviet Union : Compilation and Methodological Issues - Montanjees, Marie (Washington, D.C. : International Monetary Fund, 1995)
The IMF Working Papers series is designed to make IMF staff research available to a wide audience. Almost 300 Working Papers are released each year, covering a wide range of theoretical and analytical topics, including balance of payments, monetary and fiscal issues, global liquidity, and national and international economic developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet